Recognition of and treatment recommendations for oligometastatic disease in multidisciplinary tumor boards. (January 2023) - Christ, Sebastian M.; Heesen, Philip; Muehlematter, Urs J.; Pohl, Kaspar; William Thiel, Gabriel; Willmann, Jonas; Ahmadsei, Maiwand; Kroese, Tiuri E.; Mayinger, Michael; Balermpas, Panagiotis; Wicki, Andreas; Andratschke, Nicolaus; et al.
Highlights: More than half of oligometastatic cases went through tumor boards at our center. The frequency of use of tumor boards for oligometastatic cases is encouraging. A recommendation incl. definitive local therapy was fairly common in this series. In the absence of phase III study results, decision-making happens case-by-case. Abstract: Background and introduction: Growing evidence supports a combined modality treatment strategy for patients with oligometastatic disease. However, lack of phase III trial data and uncertainties around patient selection highlight the importance of multidisciplinary tumor boards (MDT) in therapeutic decision-making. This study aimed to analyze the recognition of and treatment recommendations for oligometastatic patients by MDTs at a large comprehensive cancer center in order to better understand current treatment patterns of oligometastasis. Materials and methods: For this retrospective single-center cross-sectional study, oligometastatic patients were identified by screening oncological PET and concurrent brain MRI scans conducted at our center in 2020. MDT discussions and recommendations within four weeks of the imaging diagnosis of oligometastasis were analyzed. Logistic regression analysis was used to identify predictors for the addition of local therapy to standard-of-care. Results: A total of 787 oligometastatic cases were identified. Lung cancer and mesothelioma, skin cancer, and prostate cancer were the most common histologies with 231 (29 %), 160 (20 %), and 84 (11 %) cases, respectively. Almost half of the cases (46 %) had one distant metastasis on imaging only. More than half (56 %) of all oligometastatic cases were discussed at an MDT. In 47 % of cases, for which a therapeutic recommendation was reached in an MDT, local therapy was part of the therapeutic strategy. On logistic regression analysis, oligometastatic skin cancer was significantly associated with a recommendation for local therapy (p < 0.05), whereas the number of oligometastases was not (p = 0.202). Conclusion: More than half of oligometastatic cases were discussed in MDTs, of which more than every second received a recommendation including the addition of local therapy. This frequency of MDT use underscores the importance of multidisciplinary decision-making, yet efforts should be increased to standardize reporting and use standard nomenclature on oligometastasis in MDTs to better frame multidisciplinary discussion.